Inequality, Advantage and the Capability Approach. Issue 1 (2nd January 2018) - Burchardt, Tania; Hick, Rod
Abstract : Inequality has acquired a newfound prominence in the academic and political debate. While scholars working with the capability approach (CA) have succeeded in influencing the conceptualisation and measurement of poverty, which is increasingly understood in multidimensional terms, recent scholarship on inequality focusses overwhelmingly on economic forms of inequality, and especially on inequalities in income and wealth. In this paper, we outline how the conceptual framework of the CA (focussing on ends rather than means, multidimensionality, and recognising the value of freedoms as well as attained functionings) has the potential to enrich the study of distributional inequality through offering a rationale for why inequality matters, exploring the association between different forms of inequality, and providing an analysis of power. But applying the CA in the context of advantage exacerbates some existing challenges to the approach (defining a capability list, and the non-observability of capabilities) and brings some fresh ones (especially insensitivity at the top of the distribution). We recommend a stronger and clearer distinction between concepts and measures. Capability inequality is a more appropriate and potentially revealing conceptual apparatus, but economic resources are likely to remain a crucial metric for understanding distributional inequality for the foreseeable future.